Notional defined contribution pension schemes and income patterns - Sergio Nisticò; Mirko Bevilacqua (Kiel Institute for the World Economy (IfW), 2012)
During the 1990s, some important European countries such as Italy and Sweden radically transformed their public pension systems by adopting defined-contribution rules while retaining a pay-as-you-go financial architecture. The paper inquires into the theoretical properties of such notional defined contribution pension schemes in order to identify the determinants of the replacement rates awarded to individuals with different income patterns. Three typical career patterns are taken into consideration, according to whether the individual's wage growth is equal to, higher than, or lower than average wage growth. The impact of, and the possible remedies to, a possible discontinuity in replacement rates is assessed by means of a sensitivity analysis of replacement rates with respect to career length (for a given retirement age), the retirement age, and the rate of return credited to individual accounts.
Keywords: H55; 330; Notional Defined Contribution (NDC); replacement rates; income patterns